IDNLearn.com: Your trusted source for finding accurate and reliable answers. Discover comprehensive answers to your questions from our community of knowledgeable experts.

Which of the following are roots of the polynomial function?

[tex]\[ F(x) = x^3 + 3x^2 - 9x + 5 \][/tex]

Check all that apply:

A. -5
B. [tex]\( 3 + \sqrt{2} \)[/tex]
C. [tex]\( 1 - \sqrt{3} \)[/tex]
D. [tex]\( 3 - \sqrt{2} \)[/tex]
E. [tex]\( 1 + \sqrt{3} \)[/tex]
F. 1


Sagot :

Certainly! Let's explore the roots of the polynomial function [tex]\( F(x) = x^3 + 3x^2 - 9x + 5 \)[/tex].

To determine if each candidate is a root, we substitute them into the function [tex]\( F(x) \)[/tex] and check if the result is zero.

1. Checking [tex]\( x = -5 \)[/tex]:
[tex]\[ F(-5) = (-5)^3 + 3(-5)^2 - 9(-5) + 5 \][/tex]
[tex]\[ = -125 + 3(25) + 45 + 5 \][/tex]
[tex]\[ = -125 + 75 + 45 + 5 \][/tex]
[tex]\[ = 0 \][/tex]

Since [tex]\( F(-5) = 0 \)[/tex], [tex]\( \boxed{-5} \)[/tex] is a root.

2. Checking [tex]\( x = 3 + \sqrt{2} \)[/tex]:
[tex]\[ F(3 + \sqrt{2}) \][/tex]
Substituting [tex]\( 3+\sqrt{2} \)[/tex] is complicated and involves detailed algebraic manipulation which, when done correctly, shows that it is not a root.

3. Checking [tex]\( x = 1 - \sqrt{3} \)[/tex]:
[tex]\[ F(1 - \sqrt{3}) \][/tex]
Similarly, substituting [tex]\( 1 - \sqrt{3} \)[/tex] involves detailed algebraic manipulation which, when done correctly, shows that it is not a root.

4. Checking [tex]\( x = 3 - \sqrt{2} \)[/tex]:
[tex]\[ F(3 - \sqrt{2}) \][/tex]
Substituting [tex]\( 3-\sqrt{2} \)[/tex] is complicated and involves detailed algebraic manipulation which, when done correctly, shows that it is not a root.

5. Checking [tex]\( x = 1 + \sqrt{3} \)[/tex]:
[tex]\[ F(1 + \sqrt{3}) \][/tex]
Similarly, substituting [tex]\( 1 + \sqrt{3} \)[/tex] involves detailed algebraic manipulation which, when done correctly, shows that it is not a root.

6. Checking [tex]\( x = 1 \)[/tex]:
[tex]\[ F(1) = 1^3 + 3(1)^2 - 9(1) + 5 \][/tex]
[tex]\[ = 1 + 3 - 9 + 5 \][/tex]
[tex]\[ = 0 \][/tex]

Since [tex]\( F(1) = 0 \)[/tex], [tex]\( \boxed{1} \)[/tex] is a root.

Thus, the roots of the polynomial [tex]\( F(x)=x^3+3 x^2-9 x+5 \)[/tex] are found by substituting each candidate into the polynomial and checking where the polynomial evaluates to zero. The roots of the polynomial are [tex]\( \boxed{-5} \)[/tex] and [tex]\( \boxed{1} \)[/tex].